1980
DOI: 10.1159/000155950
|View full text |Cite
|
Sign up to set email alerts
|

Clumping and Consistency in Primates’ Patterns of Range Use: Definitions, Sampling, Assessment and Applications

Abstract: A method for understanding how patterns of range use are related to either environmental or to social factors is first to assess quantitatively characteristics of the patterns with descriptive indices, and second, to use appropriate univariate or multivariate methods to determine the proportion of variation in the patterns associated with immediate ecological or social factors. This paper is focused on methods for quantitative assessment of two characteristics of patterns of range use: the degree to which occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…One disadvantage of equations 1-3 is that 2 separate measures are required to quantify overlap rather than a single (nondirectional) measure that reflects the degree of similarity in the 2 animals' UDs. Alternatively, Rasmussen (1980) suggested applying Spearman's correlation coefficient (Zar 1996), r s , to nonparametric estimates of the UDs obtained using a grid cell method (White and Garrott 1990). Kernohan et al (2001) discussed some of the limitations of this approach.…”
Section: Indices Of Overlapmentioning
confidence: 99%
“…One disadvantage of equations 1-3 is that 2 separate measures are required to quantify overlap rather than a single (nondirectional) measure that reflects the degree of similarity in the 2 animals' UDs. Alternatively, Rasmussen (1980) suggested applying Spearman's correlation coefficient (Zar 1996), r s , to nonparametric estimates of the UDs obtained using a grid cell method (White and Garrott 1990). Kernohan et al (2001) discussed some of the limitations of this approach.…”
Section: Indices Of Overlapmentioning
confidence: 99%
“…Distribution and abundance of resources have been reported as environmental factors influencing range use of other primates (Altmann and Altmann, 1970;Clutton-Brock, 1977;Rasmussen, 1980;Strier, 1987;Kaplin, 2001). Similarly, Turner (2000) found that food distribution might be the key element determining how chimpanzees in the semi-evergreen gallery forest of Kasoje at Mahale (Tanzania) utilize their home range.…”
Section: Habitat Preference and Fruit Availabilitymentioning
confidence: 99%
“…The use of different height classes during feeding activity was calculated as weighted averages, because sample sizes were different for each height class [25], Home range size was determined by summing all the lozenges utilized by the tamarins during the study [26], The patterns of range use were quantified by recording the occupation of each lozenge at the end of each instantaneous scan sample [27],…”
Section: Observationsmentioning
confidence: 99%